Exploring a spark-ablation setup for production of water-dispersed nanoparticles for biomedical applications - Van Oossanen, Rogier; Amaregouda, Meghana; Striekwold, Thijs; Maier, Alexandra; Denkova, Antonia G.; Godart, Jérémy; Van Rhoon, Gerard C.; Djanashvili, Kristina (Frontiers in Nanotechnology, 2025)
The interest in hybrid nanoparticles for various applications in biomedicine is growing inevitably, stimulating research towards not only more effective, but also more accessible systems. This resulted in the emergence of advanced synthetic protocols with optimized conditions for the production of nanoparticles with high yields and desired morphologies, which ultimately determine their physicochemical and biomedical properties. While these challenges were sufficient for scientists a few decades ago, the sustainability of the synthetic methods is now an important aspect. From this perspective, nanoparticle production methods based on physical principles, such as spark discharge phenomena, could provide an interesting alternative to labor-intensive and environmentally harmful chemical synthesis. The benefits of clean and sustainable physical production routes for various nanomaterials are already recognized in the fields of catalysis and electronics. Biomedicine on the other hand has been reluctant to embrace the new methodologies, as they do not inherently provide nanoparticles dispersed in aqueous media, which is essential for their safe administration and reliable physiological performance. In this work, we investigated the potential of spark discharge as an alternative method to produce hybrid palladium/iron oxide nanoparticles intended for cancer thermo-brachytherapy by leveraging the magnetothermal properties of iron and the favorable radioactive features of the palladium radioisotope. Focusing on the aqueous harvesting of the nanoparticles produced in VSParticle’s spark discharge generator, we determined the optimal settings compatible with the connected bubbling column and identified the pitfalls and possible solutions to the intrinsic challenges, such as low yields and aggregation.